Two men in front of building with sign for Dr. A.H. Bryant, Skagway, probably between 1897 and 1899 - Warner, Arthur Churchill, 1864-1943 (1897)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. Warner 102 Filed in Alaska series.